2017
DOI: 10.21767/2576-3903.100011
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Red Cell Distribution Width and Mortality in Pediatric Acute Lymphoblastic Leukemia

Abstract: Background: Red cell distribution width (RDW) is one of the standard parameters with blood cell counts. Studies have revealed that RDW could be used as a predictor of mortality in different contexts. However, data about the relation of RDW with hematologic malignancies is limited. In this research, we evaluated the relation of RDW with mortality in pediatric acute lymphoblastic leukemia (ALL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…we did not find any prognostic impact of RDW on either OS or DFS in adult ALL. This finding was consistent with a study exploring the prognostic impact of RDW in children ALL [15]. Although this was a single-center retrospective extended analysis, pretreatment grade 4 thrombocytopenia was an independent negative prognostic factor of both overall survival and disease-free survival in adults with acute lymphoblastic leukemia.…”
Section: Resultssupporting
confidence: 90%
“…we did not find any prognostic impact of RDW on either OS or DFS in adult ALL. This finding was consistent with a study exploring the prognostic impact of RDW in children ALL [15]. Although this was a single-center retrospective extended analysis, pretreatment grade 4 thrombocytopenia was an independent negative prognostic factor of both overall survival and disease-free survival in adults with acute lymphoblastic leukemia.…”
Section: Resultssupporting
confidence: 90%
“…RBCs, hemoglobin and Platelets exhibited low count levels when compared with normal reference range as shown in Table 4, whereas WBC count was high in leukemia cases. Low levels of RBC, 36 hemoglobin Okuku et al 37, 38 ); platelet 2,17,39 are very common in leukemic subjects whereas, high WBC count which is one of the characteristics of leukemia is also observed by other research workers 17,40,41 . WBC differential count also showed statistically significant values, when compared with normal reference value, neutrophil, monocyte, and eosinophil showed lower mean values, whereas lymphocytes level was high.…”
Section: Resultsmentioning
confidence: 67%
“…When specifically analyzing RDW and mortality among pediatric leukemia patients, half of the 12 patients who died (14.5% of the study population) had an RDW over the cut-off point of 15.7 which was not statistically significant (p ¼ 0.09). 4 Lastly, a study by Khanbabaee et al showed that though RDW correlated significantly with mortality on the day of admission to the PICU, specifically for patients diagnosed with sepsis, correlation waned over time and did not appear to predict mortality by day 8. 13 Multiple pathophysiological connections exist between dyserythropoiesis and clinical outcomes, and thus are reasonable hypotheses that support the results determined from this meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Nutritional deficiencies and inflammation coupled with comorbidities, such as hypoxemia and intravascular erythrocyte destruction, may further exacerbate marrow stress and reflect in the RDW value. Elevated RDW has been shown to correlate with mortality rates in adult and pediatric patients [1][2][3][4][5][6][7][8] highlighting the utility of RDW as a surrogate marker for the pathophysiology of critical illness.…”
Section: Introductionmentioning
confidence: 99%